Validity and reliability of the Turkish version of the hand-use-at-home questionnaire for children with unilateral cerebral palsy and neonatal brachial plexus palsy - KARADAĞ SAYGI, NAİME EVRİM (My University, 2023)
Purpose: To translate the Hand-Use-at-Home questionnaire (HUH), assesses the amount of spontaneous use of the affected hand in children with 18 bimanual activities, into Turkish and examine its validity and reliability on children with neonatal brachial plexus palsy (NBPP) or unilateral cerebral palsy (UCP). Materials and methods: The HUH was translated and cross-culturally adapted to Turkish and administered to children with NBPP (n = 25) and UCP (n = 42) between 3 and 10 years. The psychometric analyses included reliability by internal consistency (Cronbach’s alpha) and test/retest reliability (intraclass correlation coefficient, ICC) structural validity was evaluated with exploratory factor analysis, and construct validity was investigated by matching the HUH with the Pediatric Outcome Data Collection Instrument Upper Extremity Scale (PODCI) (NBPP only), and Children’s Hand-Use Experience Questionnaire (CHEQ) (UCP only). Results: HUH showed excellent test–retest reliability (ICC2,1 = 0.988 Cl (0.977–0.992)), excellent internal consistency (Cronbach’s-α = 0.989), and moderate correlation with CHEQ (rs = 0.558) in UCP and high correlation with PODCI Scale (rs = 0.789) in NBPP group. The HUH had low and moderate correlation respectively lesion-extent levels (r=-0.457) in NBPP and 5 Manual Ability Classification System levels (r=-0.688) in the UCP group. Conclusion: The HUH is a valid and reliable tool to assess the amount of spontaneous use of the affected hand in Turkish children with NBPP and UCP.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Rehabilitasyon; Rehabilitation; Brachial plexus; cerebral palsy; hand function; pediatric rehabilitation; upper extremity; Brachial plexus; cerebral palsy; hand function; pediatric rehabilitation; upper extremity